Ginásio Auxilium de Anápolis/GO (1943-1961): a formação da ‘fina flor’ da sociedade - Mendonça, Roselene Candida Barroso (2023)
This dissertation's theme is female formation at the Ginásio Auxilium of Anápolis/GO, from 1943 to 1961, in which we sought to understand the school culture present in the Catholic institution, based on the testimonies of its graduates. The school was created by the Salesian Sisters to exclusively serve women. The central question of the research was: What was female secondary education like at the Ginásio Auxilium of Anápolis/GO (1943-1961)? In view of this, we sought to analyze female secondary education at the Ginásio Auxilium of Anápolis/GO during the aforementioned period. The period stipulated for the research refers to the initial year in which the exclusively female secondary course was implemented in Anápolis/GO, through the creation of the Ginásio Auxilium, under the guidelines of Decree-Law no. 4,244/1942, which provided for secondary education and made distinctions for women's education, until the implementation of Law no. 4,024/1961. The study falls within the research field of History of Education and adopts cultural history as its historiographical conception, proposing an analysis of the school culture that permeated the researched institution. The main authors used were: Chartier (1990), Chervel (1990) and Julia (2001). The research is qualitative and adopts as means of investigation: ibliographical research, document analysis and interview analysis. As a result, it was found that Brazilian elites, mainly men, were privileged in access to high school education. Women were included in this educational stage at the end of the 19th century. In Goiás, the expansion of this educational level occurred with the arrival of religious congregations, with the implementation of confessional schools, predominantly private. The Ginásio Auxilium of Anápolis followed the legal guidelines imposed by Decree-Law no. 4,244/1942, as well as the religious assumptions of the Catholic Church, which aimed to form a good Christian and honest citizen, and the guidelines of Don Bosco, whose educational principle was based on reason, religion and amorevollezza. In this way, the institution's school culture was permeated by religiosity, morals, civics and patriotism. The education offered was considered to be of high quality, with a traditionalist approach, which sought, through the action of religious teachers, to form the ‘fine flower’ of Anapolis society – girls from wealthy families, who needed a refined education, forming the mother, wife and ideal housewife, and then the professional, reproducing the teachings obtained at the institution.